Autonomous detection, navigation, and propulsion for satellites - Badger, Stanley (Kansas State University, 2009)
With the increasing number of satellites and space debris in all orbits the need for individual satellites to be able to autonomously detect and determine methods to navigate around them is increasing. Even with continued input and control from a ground station, the ability for a satellite to act to save itself from obstacles not visible from ground stations, or if communications were temporarily lost could be key to saving millions of dollars in hardware as well as improving overall performance and operational lifetimes.
Keywords: Autonomous; Detection; Navigation; Propulsion; Satellites; Engineering, Electronics and Electrical (0544)